CiteSpace-based visualization and analysis of hotspots and development trends in childbirth experience research - Shi, Jie; Wang, Yan; Luo, Jieling; Jiang, Hailong; Geng, Xiaoting; Xiang, Mengyuan; Li, Shuying (Frontiers in Global Women's Health, 2025)
ObjectiveTo explore and analyze the current research status, hotspots, and development trend of labor and delivery experience, to provide a reference for subsequent related research and clinical practice.MethodsWe searched the Web of Science database for literature related to labor and delivery experience published between its establishment and December 20, 2024, and conducted bibliometric analysis using CiteSpace software.ResultsAfter screening, 1089 papers were included in the analysis, and the number of annual publications showed a growing trend, reaching its highest in 2024. The United States and Sweden dominated the list. The research hotspots focused on maternal mental health, delivery methods, and quality of Intrapartum care.ConclusionThe field of birth experiences is currently undergoing rapid development, with leading trends including innovations in delivery methods, prenatal care, research in the cognitive neuroscience of childbirth, and a focus on mothers undergoing induced labor and those in low-income areas to optimize the overall birth experience.